IKHTIAR MANUSIA DALAM FILSAFAT MULLA SHADRA - Riko Putra (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Endeavor becomes a mandatory act that humans undergo in life in order to find goodness and happiness in life, making the doer choose to act as anaction for the goodness of life. This is a command in the Islamic religion which is contained in the holy book of the Quran and has become a special concern for several philosophers. Mulla Shadra as one of the modern Muslim philosophers has his own concep tregarding the endeavor. In this article, the author tries to present the thoughts of the Muslim philosopher Mulla Shadra about endeavor and several verses of the Quran about endeavor. The method that the authoruses in discussing this is the critical analysis method. This study resulted in the discovery that Mulla Shadra's thoughts about endeavor are that humans have the power of reason as guidance from God that can determine their own actions, which is indicated by the maturity of reason before acting.